Variation of Small and Large Wild Bee Communities Under Honeybee Pressure in Highly Diverse Natural Habitats - Demeter, Imre; Balog, Adalbert; Sárospataki, Miklós (Frontiers in Ecology and Evolution, 2021)
During the study, honey bee effects on wild bees were tested and hypothesized that smaller distances from beehives will increase competitions between honey bees and wild bees, while greater distances will have a deleterious effect on competition. The impact to species richness and diversity were tested with distances from beehives, considering that this may differ when large and small wild bee species are considered separately. Altogether 158 species and 13164 individuals were collected, from which 72% (9542 individuals) were A. mellifera. High variation in abundances were detected from one year to another, the species turnover by sites were 67% in site A, 66% in site V and 63% in site F. This last one was the site with previous contact with honey bees. Considering distances from beehives, significant decreases in small bee species diversity were detected from one year to another at each distances except site F, 250 m from hives. Change in species diversity and community structure of small bee species are detected from one year to another.